2014
DOI: 10.1371/journal.pone.0109001
|View full text |Cite
|
Sign up to set email alerts
|

Fitness of Crop-Wild Hybrid Sunflower under Competitive Conditions: Implications for Crop-to-Wild Introgression

Abstract: Understanding the likelihood and extent of introgression of novel alleles in hybrid zones requires comparison of lifetime fitness of parents and hybrid progeny. However, fitness differences among cross types can vary depending on biotic conditions, thereby influencing introgression patterns. Based on past work, we predicted that increased competition would enhance introgression between cultivated and wild sunflower (Helianthus annuus) by reducing fitness advantages of wild plants. To test this prediction, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 49 publications
2
30
0
Order By: Relevance
“…, Mercer et al. ). Thus, following a hybridization event where wild, F 1 , and crop plants each produce crop–wild hybrid seeds, the substantial number of surviving seedlings has the potential to cross and backcross with each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Mercer et al. ). Thus, following a hybridization event where wild, F 1 , and crop plants each produce crop–wild hybrid seeds, the substantial number of surviving seedlings has the potential to cross and backcross with each other.…”
Section: Discussionmentioning
confidence: 99%
“…The three removal dates were as follows: late fall (removed on December 10, 2010), for monitoring maladaptive fall germination; early spring (removed on March 8, 2011), for investigating early germination; and spring (removed on April 8, 2011), for capturing peak emergence. Removal dates were selected based on a previous seed burial study at this location conducted from 2009 to 2010 Mercer et al 2014). Each block was then covered by hardware cloth to prevent seed predation.…”
Section: Field Seed Burial Experimentsmentioning
confidence: 99%
“…However, seed production can be lower among crop–wild hybrid sunflower cross types than wild plants, although differences diminish under more competitive conditions (Mercer et al. ). Thus, predicting the occurrence of demographic swamping is not straight forward and conclusions will likely hinge on both the fitness measure used and the hybrid zone environment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, although Brassica rapa and B. napus both suffered when in competition with Lolium perenne , plant density, regardless of species, had a greater impact on performance, even in the presence of insect herbivore pressure (Damgaard & Kjaer, ). Similarly, conspecific plant density had a greater influence on fitness parameters of sunflower and crop‐wild hybrids than did the presence of interspecific competition from other weed species (Mercer et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Results from the growth chamber‐grown plants indicate potential for complex fitness effects that could ultimately influence transgene establishment (Chan et al., , ). Several studies have indicated the importance of evaluating fitness based on performance throughout the life cycle, in a range of environments, and under competitive conditions (Agren et al., ; Bhatnagar‐Mathur et al., ; Hartman et al., ; Mercer et al., ; Mittler & Blumwald, ). Therefore, in these experiments, we sought to examine fitness impacts of overexpression of the three mechanistically different abiotic stress resistance transgenes ( CBF3, M6PR, SOS1 ) in A. thaliana as observed throughout the life cycle over six generations in variable field environments, and to monitor transgene persistence when in competition with wild‐type (WT) plants as would occur during introgression into natural populations.…”
Section: Introductionmentioning
confidence: 99%